Isometric Timelike Helicoidal and Rotational Surfaces in 4–Dimensional Minkowski Space - Demirci, Burcu Bektaş; Babaarslan, Murat; Küçükarıkan, Yasin (University of Nis, 2025)
In this paper, we examine classical Bour’s theorem for timelike helicoidal surfaces in 4- dimensional Minkowski space. Then, we characterize a pair of isometric helicoidal and rotational surface which have same Gauss map. Also, we provide the parametrizations of such isometric surfaces. Finally, we introduce some examples and plot the corresponding graphs by using Wolfram Mathematica 10.4.
Keywords: Bour’s Theorem; Helicoidal Surface; Rotational Surface; Gauss Map; Mean Curvature; Minkowski Space